Psicoterapia grupal no transtorno obsessivo-compulsivo - Torres, Albina Rodrigues [UNESP]; Lima, Maria Cristina Pereira [UNESP]; De Abreu Ramos-Cerqueira, Ana Teresa [UNESP] (My University, 2001)
There are few published papers about group psychotherapy for patients with obsessive-compulsive disorder (OCD), and usually restricted psychoeducational, support or cognitive-behavioral approaches. This article describes the experience of group psychotherapy for OCD patients started in 1996 in Botucatu Medical School - Unesp, São Paulo, Brazil. The two-hour sessions occur once a month, with 6 to 10 female patients, and are based on psychodramatic techniques. Psychotropic prescriptions are given after the sessions. In the beginning, aggressive obsessions were more prominent and were reported with much anguish and shame. Gradually, the themes changed from OCD specific issues (symptoms, pharmacological treatment, outcome, need of exposure and response prevention) to deeper and more personal psychodynamic aspects. The psychodramatic approach (techniques of double, mirror, role inversion, search for prymary scenes) has mostly shown: difficulty in accepting their own human mistakes or negative emotions due to excessive personal demands. This seems to generate guilt, low self-esteem, idealization of others, difficulty in enjoying pleasant situations, fear of taking responsibilities and of losing control (madness/aggressiveness). The group has been considered very important by the patients, since sharing experiences helps to diminish feelings of isolation, shame and guilt, stimulates the exposure to feared situations and enhances self-esteem. The fact that all participants have the same disorder favors group cohesion and provides relief, as they see in the others some of their afflictions and are able to share similar feelings and experiences. Many times the burden of the symptoms are dealt with humor. The confidence in such therapeutic setting is helping the identification and resolution of personal conflicts and contributing to the adherence to pharmacological treatment. The group also provides valuable training experiences for resident physicians in psychiatry.
Group psychotherapy for obsessive-compulsive disorder
Keywords: Group psychotherapy; Obsessive-compulsive disorder; Psychodramatic approach; Psychodynamic aspects; Psychotherapeutic treatment; psychotropic agent; aggression; aggressiveness; behavior therapy; Brazil; cognitive therapy; conflict; double technique; emotion; environmental exposure; experience; fear; female; group dynamics; group therapy; guilt; human; mirror technique; obsessive compulsive disorder; outcomes research; patient compliance; patient education; prescription; psychiatry; psychodrama; psychodynamics; publication; residency education; role inversion; role playing; search for primary scenes technique; self esteem; shame; social isolation; stimulus response; symptom